A 5'-3' exonuclease from Saccharomyces cerevisiae is required for in vitro recombination between linear DNA molecules with overlapping homology. - Huang, K N (1993)
When two linear DNA molecules with overlapping, homologous ends were incubated with a yeast nuclear extract, they recombined at the region of homology to produce a joint molecule. We have identified a 5'-3' exonuclease in the extract that is likely to be responsible for the formation of the observed product. We propose that the exonuclease degrades each substrate to reveal regions of complementary sequence which anneal to form a recombinant product. Consistent with this model, we have partially purified the activity that promotes joint molecule formation and found it to cofractionate with a 5'-3' exonuclease activity through three consecutive chromatography steps. We have further characterized the reaction to determine the optimal length of homology. Substrates with homologous terminal overlaps of 29 to 958 bp were capable of product formation, whereas substrates with longer overlaps were not. Extracts prepared from a number of recombination-defective or nuclease-deficient strains revealed no defect in exonuclease activity, indicating that the reaction is likely to be dependent upon the product of an as yet unidentified gene.